2020
DOI: 10.3390/molecules25081819
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effects of β-Glucans, Mannans, and Fucoidans: Mechanism of Action and Their Prospects for Clinical Application

Abstract: The search for lipid-lowering drugs is important for clinical medicine. This review summarizes our research findings regarding the hypolipidemic activity of polysaccharides. There are several validated agents altering lipid levels which reduce the risk of atherosclerotic cardiovascular events. Nonetheless, for many people, the risk of such an event remains unacceptably high despite treatment with these agents. This situation has prompted the search for new therapies to reduce the residual cardiovascular risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 100 publications
2
19
0
Order By: Relevance
“…Consistent with our results, another meta-analysis of clinical trials showed that β-glucan has a lowering effect on LDLc, non-HDLc and apoB [26]. Although oat and yeast β-glucans have some chemical differences, a previous study showed that as long as the purity of β-glucan is high, there is no difference among the sources of β-glucans [43,80].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, another meta-analysis of clinical trials showed that β-glucan has a lowering effect on LDLc, non-HDLc and apoB [26]. Although oat and yeast β-glucans have some chemical differences, a previous study showed that as long as the purity of β-glucan is high, there is no difference among the sources of β-glucans [43,80].…”
Section: Discussionsupporting
confidence: 90%
“…The dyslipidemic rat model was generated using Triton WR 1339. The agent was widely used to study the lipid metabolism status in experimental animals and did not involve inducing great dramatic changes in blood parameters and has minor side effects and is the model of choice when study lipid profile [ 19 ]. Serum cholesterol and triglycerides were elevated in the sera of experimental rats after a single dose of Triton WR 1339 ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum cholesterol and triglycerides were elevated in the sera of experimental rats after a single dose of Triton WR 1339 ( Table 3 ). Records proved that the normalization usually occurred after 10 days after the administration of treatment agents [ 19 ]. The importance of such a study come to introduce a base of elucidation for the ability of FSK to normalize lipid profile and stimulate lipolysis, especially in omental adipose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The β-glucans from cereals, mainly from barley and oats, have been considered as prebiotics [7,8], and the consumption of these compounds has been related to health benefits [9]. In addition to the fact that these compounds are part of the functional dietary fibers, their fermentation in the gastrointestinal tract could be the origin of those benefits [10][11][12][13]. However, the main importance is that they directly affect both the growth of probiotic microorganisms and the activation of their proteolytic system [14][15][16].…”
Section: Introductionmentioning
confidence: 99%